Evaluation of the Ad Hoc Organizing Body for the 2020 Regional Head Election Amid the Covid 19 Pandemic in Tomohon City - Tindangen, Masye Freike; Lumingkewas, Lexie; Kairupan, Sisca Beatris (Technium Social Sciences Journal, 2023)
This study aims to evaluate the Ad Hoc Organizing Body for the 2020 Regional Head Election amid the Covid Pandemic in Tomohon City. This research approach uses a descriptive qualitative approach, with a total of 10 informants with data collection techniques namely observation, interviews and documentation with data analysis techniques through data reduction, data presentation and verification of conclusions. The results of this study indicate that the process of the Ad Hoc Organizing Body for the Election of Regional Heads of Tomohon City still has problems, including those related to the socialization and information sharing processes that have not been carried out massively. according to the workload so that it affects the quality of work. Furthermore, it was found in the communication sub focus, namely the lack of enforcement from leaders to subordinates or between commissioners and the formation of members related to weak communication that was built and a lack of initiative from them as parties with authority. to order friends who are other people and even other committees to provide communication to other people. Then the next problem was found in the sub-focus of the Integrity of Ad Hoc Organizing Bodies, namely that there were still several administrators of Ad Hoc institutions who carried out gratuities where gratuities were contrary to integrity.